2021
DOI: 10.1038/s42003-021-02111-3
|View full text |Cite
|
Sign up to set email alerts
|

PD-L2 suppresses T cell signaling via coinhibitory microcluster formation and SHP2 phosphatase recruitment

Abstract: The coinhibitory receptor, PD-1, is of major importance for the suppression of T cell activation in various types of immune responses. A high-resolution imaging study showed that PD-1 forms a coinhibitory signalosome, “PD-1 microcluster”, with the phosphatase, SHP2, to dephosphorylate the TCR/CD3 complex and its downstream signaling molecules. Such a consecutive reaction entirely depended on PD-1–PD-L1/2 binding. PD-L2 is expressed on professional antigen-presenting cells and also on some tumor cells, which po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This signalosome suppresses T-cell responses. Similar to the effect of anti-PD-L1 agents, PD-L2 blockade may exert anti-tumor effects, although no therapeutic agents target PD-L2 ( 10 ). In the future, anti-PD-L2 agents are expected to be used to treat all types of cancer.…”
Section: The Function Of Pd-1 and Ctla-4mentioning
confidence: 99%
“…This signalosome suppresses T-cell responses. Similar to the effect of anti-PD-L1 agents, PD-L2 blockade may exert anti-tumor effects, although no therapeutic agents target PD-L2 ( 10 ). In the future, anti-PD-L2 agents are expected to be used to treat all types of cancer.…”
Section: The Function Of Pd-1 and Ctla-4mentioning
confidence: 99%
“…Recent clinical reports have described malignant tumors with high expression of human (h) PD-L2 or with dual expression of hPD-L1 and hPD-L2 as a ligand for hPD-1 4 . As such, in our previous report, we con rmed the endogenous expression of hPD-L1 and hPD-L2 by different cell lines of human lung cancers before or after in vitro culture with interferon γ (IFNγ) and found various patterns of hPD-1 ligand expression depending on each line 5 . Many types of ICIs have been developed and approved for therapies of these types of cancers all over the world.…”
Section: Introductionmentioning
confidence: 73%
“…Previous reports have shown that the recruitment of SHP2 to PD-1 microclusters occurs transiently and quickly after mPD-1 is crosslinked by mPD-L1 or mPD-L2. The clustering of SHP2 would take just tens of seconds 5,11 . In contrast, other reports have biochemically demonstrated that human SHP2 was immediately recruited to the cytoplasmic tail of hPD-1, while the colocalization of hSHP2 at hPD-1 tends to be more prolonged than mPD-1 with mSHP2 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death protein 1 (PD-1) signaling Some tumors express PD-L1, which contributes to immune evasion by inhibiting cytotoxic responses. Thus, anti-PD-1/PD-L1 antibodies can promote T cell activation and enhance anti-tumor immunity by blocking the interaction between PD-1 and PD-L1/PD-L2 [270,271]. Typically, PD-L1 or PD-L2 are expressed on the surface of cancer cells or antigen-presenting cells and transduce a signal for cooperation with PD-1 expression on the cell surface of T lymphocytes to stimulate restraint signaling [272,273].…”
Section: 11mentioning
confidence: 99%